Scale Space and Variational Methods in Computer Vision: 5th International Conference, SSVM 2015, Lège-Cap Ferret, France, May 31 - June 4, 2015, Proceedings - Aujol, Jean-François (Lecture notes in computer science, 2015)
Scale space and partial differential equation methods -- Denoising, restoration and reconstruction, segmentation and partitioning -- Flow, motion and Registration -- Photography, texture and color processing.-Shape, surface and 3D Problems -- Optimization theory and methods in imaging.
Literaturangaben
Keywords: Konferenzschrift; Level-Set-Methode; Variationsrechnung; Geometrieverarbeitung; Bildverarbeitung; Rauschunterdrückung; Skalenraum; Merkmalsextraktion; Maschinelles Sehen